Kaitan Mental Accounting Dan Perilaku Keuangan Terhadap Keputusan Investasi Investor Milenial Post Pandemi Covid 19 - Prawitasari, Putu Putri (Fakultas Ekonomi Universitas Negeri Manado, 2024)
The Covid-19 pandemic has made online purchases increase quite dramatically. T The focus of mental accounting is how one should respond and evaluate a situation when there are two or more possible outcomes. The concept of behavioral finance takes into account various types of investors in the perception of risk associated with investment decisions. In this study, an analysis was carried out regarding how the influence of Mental accounting and Behavioral finance owned by Millennial investors in Denpasar on investment decisions. The sample was taken using a purposive sampling technique, so that the total sample is 100 millennial investors. The results of this study show that mental accounting and behavioral finance positively and significantly influence the investment decisions of millennial investors in Denpasar.